ANALYSIS OF ISLAMIC BRAND IMAGE AND FACILITIES ON CUSTOMER DECISION MAKING TO CHOOSE BMT BERINGHARJO FINANCIAL INSTITUTION PONOROGO BRANCH WITH TRUST AS A MEDIATING VARIABLE - kurniawan, dhika amalia; alamsyah, Robi Sugih; Rusli, Latifah; Maemunah, Hayatul (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2024)
The purpose of this study is to analyze the influence of Sharia Brand Image and Facilities on consumer decisions to use BMT Beringharjo Ponorogo financial services mediated by variable trust. The results showed that the Islamic Brand Image variable has a positive influence on the decision making of members to choose BMT Beringharjo financial institutions. It can be concluded that the better the Islamic Brand Image carried out by BMT Beringharjo, the more confident members choose BMT Beringharjo as their financial institution. The facility variable has a positive influence on the decision making of members choosing BMT Beringharjo financial institutions so that H2 is accepted. This happens because the facilities offered by BMT Beringharjo are in accordance with the needs of members and avoid ribawi elements. Trust variables can mediate between Sharia Brand Image on the decision of members to choose financial institutions because Sharia Brand Image has a significant positive effect, this is because the better the Sharia Brand Image owned by BMT Beringharjo, the higher the member's trust in the financial institution. 4. Trust variables can mediate between facilities and decision making of members choosing financial institutions at BMT Beringharjo. This is because BMT serves its members honestly, transparently and reliably in meeting member needs.